A multiple case study on factors affecting ICO success - Panin, Aleksei (2019)
Blockchain and Initial Coin Offering (ICO) hold incredible potential in our world today. The opportunities of these technologies are believed to be going further beyond the horizon; ICO helps start-ups succeed in receiving sufficient investments for their projects, and subsequently succeed in developing and creating necessary and useful blockchain based applications into society. This paper investigates the factors that are positively affecting firms’ ability to meet their fundraising goals via ICO. This set of factors if identified from existing literature and up-to-date information derived from hands-on experience of eight firms that have already completed their ICOs with different achievement level of their maximum fundraising goals. This work concludes that prior to conducting an ICO, managers should build first a strong backbone of the company. Regardless of crypto market specifics, ICO companies, like any other ones, seem to follow the same rule of doing business. Findings of the most important success factors reported by case companies included all key elements of a Business Model Canvas, and therefore managers could be advised to use this tool for planning and building a company. This study moreover investigates and finds explanation to when and why the same factors can play different role across projects with different project settings.